2013
DOI: 10.1002/gcc.22045
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous mutations in the PALB2 hereditary breast cancer predisposition gene impact on the three‐dimensional nuclear organization of patient‐derived cell lines

Abstract: PALB2/FANCN is a BRCA1- and BRCA2-interacting Fanconi Anemia (FA) protein crucial for key BRCA2 genome caretaker functions. Heterozygous germline mutations in PALB2 predispose to breast cancer and biallelic mutations cause FA. FA proteins play a critical role in the telomere maintenance pathway, with telomeric shortening observed in FA cells. Less is known about telomere maintenance in the heterozygous state. Here, we investigate the roles of PALB2 heterozygous mutations in genomic instability, an important ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Sarkar et al [25] previously established that, in mice, centromeres are located more toward the nuclear periphery in normal lymphocytes but are more concentrated in the middle of the nucleus in immortalized PreB lymphocytes and even more so in the murine plasmacytoma line MOPC460D [25]. Wark et al [20] showed that the spatial position of centromeres in interphase nuclei was altered in fibroblast cell lines with monoallelic truncating PALB2 mutations (PALB2 c.3323delA) compared to wild-type controls and fibroblasts with BRCA1 and BRCA2 mutations. This difference was found to be a contributing factor in increasing the propensity for chromosomal rearrangements [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarkar et al [25] previously established that, in mice, centromeres are located more toward the nuclear periphery in normal lymphocytes but are more concentrated in the middle of the nucleus in immortalized PreB lymphocytes and even more so in the murine plasmacytoma line MOPC460D [25]. Wark et al [20] showed that the spatial position of centromeres in interphase nuclei was altered in fibroblast cell lines with monoallelic truncating PALB2 mutations (PALB2 c.3323delA) compared to wild-type controls and fibroblasts with BRCA1 and BRCA2 mutations. This difference was found to be a contributing factor in increasing the propensity for chromosomal rearrangements [20].…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary hotspots in the pericentromeric chromosomal regions that have been implicated as major contributors to genomic instability and large-scale genetic changes such as chromosomal rearrangements, deletions, and insertions or bursts of retrotransposon activity could force centromere positions to change [16]. However, little is known about effects of those changes in the dynamics and stability of centromeres in cancer [18,19,20]. Consequently, the positioning of the centromeres in the interphase nucleus has been the focal point of several studies (e.g., [19,20,21,22,23,24]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that heterozygosity of BRCA2 as well as PALB2 results in some loss of DNA replication fork protection and a defect in DNA damage response, which contributes to genomic instability [ 38 , 39 ]. However, in the present study, single heterozygous mice and MEFs ( Brca2 Ko/+ , Brca2 G25R/+ , and Palb2 Ko/+ ) did not reveal any overt defects.…”
Section: Discussionmentioning
confidence: 99%
“…a.) and functionally associates it with BRCA2 via its amino and carboxyl (6-90 a. a specifically Leu21 and 24) terminus respectively 13,15,17,[38][39][40] . Thus, the functional partnership of BRCA1 and BRCA2 in the DDR further elaborates the genetic similarity of either protein (Figure 2) 17,34 .…”
Section: Collaborative Interaction Of Brca1-brca2-palb2-rad51 Complexmentioning
confidence: 99%